2000
DOI: 10.1006/enfo.2000.0017
|View full text |Cite
|
Sign up to set email alerts
|

Critical Review of Environmental Forensic Techniques: Part I

Abstract: A multitude of forensic techniques are available for age dating and source identi®cation, including aerial photography interpretation, corrosion models, the commercial availability of a compound, chemical associations with discrete type processes, chemical pro®ling, degradation models and contaminant transport models. These techniques, however, are rarely challenged or discussed in the literature relative to the scrutiny encountered in environmental litigation. When introduced as scienti®c evidence, the govern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 146 publications
0
22
0
3
Order By: Relevance
“…In this paper, Morrison discussed commonly used environmental forensic techniques and their possible applications so that readers can decide which technique is most appropriate for their cases. A more in-depth review of these techniques can be found in Morrison (2000b;c).…”
Section: Contaminant Transport Inversion Methodsmentioning
confidence: 99%
“…In this paper, Morrison discussed commonly used environmental forensic techniques and their possible applications so that readers can decide which technique is most appropriate for their cases. A more in-depth review of these techniques can be found in Morrison (2000b;c).…”
Section: Contaminant Transport Inversion Methodsmentioning
confidence: 99%
“…Suggs et al (2002) describe this laboratory component as "chemical fingerprinting." A limited review of some other types of environmental forensic investigation, such as underground storage tank corrosion modeling and the use of aerial photography, may be found in Morrison (2000aMorrison ( , 2000b.…”
Section: Environmental Forensic Investigations By the Nsw Epamentioning
confidence: 99%
“…Reviews of time inversion methods for 'source identification inverse problems' can be found in Morrison [25][26][27], Atmadja and Bagtzoglou [4,5], Bagtzoglou and Atmadja [7,8]. However, the widespread use of some of these methods is still limited due to their non-conventional nature.…”
Section: Introductionmentioning
confidence: 97%